Core outcome set for studies investigating management of selective fetal growth restriction in twins. (29th March 2020) - Townsend, R.; Duffy, J. M. N.; Sileo, F.; Perry, H.; Ganzevoort, W.; Reed, K.; Baschat, A. A.; Deprest, J.; Gratacos, E.; Hecher, K.; Lewi, L.; Lopriore, E.; et al.
ABSTRACT: Objective: Selective fetal growth restriction (sFGR) occurs in monochorionic twin pregnancies when unequal placental sharing leads to restriction in the growth of just one twin. Management options include laser separation of the fetal circulations, selective reduction or expectant management, but what constitutes the best treatment is not yet known. New trials in this area are urgently needed but, in this rare and complex group, maximizing the relevance and utility of clinical research design and outputs is paramount. A core outcome set ensures standardized outcome collection and reporting in future research. The objective of this study was to develop a core outcome set for studies evaluating treatments for sFGR in monochorionic twins. Methods: An international steering group of clinicians, researchers and patients with experience of sFGR was established to oversee the process of development of a core outcome set for studies investigating the management of sFGR. Outcomes reported in the literature were identified through a systematic review and informed the design of a three‐round Delphi survey. Clinicians, researchers, and patients and family representatives participated in the survey. Outcomes were scored on a Likert scale from 1 (limited importance for making a decision) to 9 (critical for making a decision). Consensus was defined a priori as a Likert score of ≥ 8 in the third round of the Delphi survey. Participants were then invited to take part in an international meeting of stakeholders in which the modified nominal group technique was used to consider the consensus outcomes and agree on a final core outcome set. Results: Ninety‐six outcomes were identified from 39 studies in the systematic review. One hundred and three participants from 23 countries completed the first round of the Delphi survey, of whom 88 completed all three rounds. Twenty‐nine outcomes met the a priori criteria for consensus and, along with six additional outcomes, were prioritized in a consensus development meeting, using the modified nominal group technique. Twenty‐five stakeholders participated in this meeting, including researchers ( n  = 3), fetal medicine specialists ( n  = 3), obstetricians ( n  = 2), neonatologists ( n  = 3), midwives ( n  = 4), parents and family members ( n  = 6), patient group representatives ( n  = 3), and a sonographer. Eleven core outcomes were agreed upon. These were live birth, gestational age at birth, birth weight, intertwin birth‐weight discordance, death of surviving twin after death of cotwin, loss during pregnancy or before final hospital discharge, parental stress, procedure‐related adverse maternal outcome, length of neonatal stay in hospital, neurological abnormality on postnatal imaging and childhood disability. Conclusions: This core outcome set for studies investigating the management of sFGR represents the consensus of a large and diverse group of international collaborators. Use of these outcomes in future trials should help to increase the clinical relevance of research on this condition. Consensus agreement on core outcome definitions and measures is now required. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.